Multiple cosmic sources for meteorite macromolecules? - Sephton, Mark A.; Watson, Jonathan S.; Meredith, Will; Love, Gordon D.; Gilmour, Iain; Snape, Colin E. (Mary Ann Liebert, 2015)
The major organic component in carbonaceous meteorites is an organic macromolecular material. The Murchison macromolecular material comprises aromatic units connected by aliphatic and heteroatom-containing linkages or occluded within the wider structure. The macromolecular material source environment remains elusive. Traditionally, attempts to determine source have strived to identify a single environment. Here, we apply a highly efficient hydrogenolysis method to liberate units from the macromolecular material and use mass spectrometric techniques to determine their chemical structures and individual stable carbon isotope ratios. We confirm that the macromolecular material comprises a labile fraction with small aromatic units enriched in 13C and a refractory fraction made up of large aromatic units depleted in 13C. Our findings suggest that the macromolecular material may be derived from at least two separate environments. Compound-specific carbon isotope trends for aromatic compounds with carbon number may reflect mixing of the two sources. The story of the quantitatively dominant macromolecular material in meteorites appears to be made up of more than one chapter.